STRATEGI PEMASARAN PADA WELU CAFE & RESTO DI KELURAHAN WOLOAN SATU UTARA KECAMATAN TOMOHON BARAT (Marketing Strategy at Welu Cafe & Resto in North Kelurahan Woloan Satu District of West Tomohon) - Meyjer Vinsensius Pangkey; Caroline B. D. Pakasi; Eyverson Ruauw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aims to determine and evaluate the marketing mix strategy at Welu Cafe & Resto. This research was conducted in January to March 2020. The data used in this study are primary and secondary data. Primary data were obtained through direct interviews with 44 respondents using a questionnaire. While secondary data is data obtained from Welu Cafe & Resto, literature and previous research. The sampling method is done by accidental sampling, which is the sample taken by chance. The results showed that the ideal score for the whole question = 3168 (very good), the lowest score = 1 (very bad). Based on data obtained from 18 questions given to 44 respondents, a total score of 1968 was obtained with a "Good" interpretation of the marketing strategy adopted by Welu Cafe & Resto.Keywords: Marketing Strategy, Welu Cafe & Resto